Evaluation of Strategies to Produce Highly Porous Cross-Linked Aggregates of Porcine Pancreas Lipase with Magnetic Properties - José Renato Guimarães; Raquel de Lima Camargo Giordano; Roberto Fernandez-Lafuente; Paulo Waldir Tardioli (Molecules, 2018)
The preparation of highly porous magnetic crosslinked aggregates (pm-CLEA) of porcine pancreas lipase (PPL) is reported. Some strategies to improve the volumetric activity of the immobilized biocatalyst were evaluated, such as treatment of PPL with enzyme surface-modifying agents (polyethyleneimine or dodecyl aldehyde), co-aggregation with protein co-feeders (bovine serum albumin and/or soy protein), use of silica magnetic nanoparticles functionalized with amino groups (SMNPs) as separation aid, and starch as pore-making agent. The combination of enzyme surface modification with dodecyl aldehyde, co-aggregation with SMNPs and soy protein, in the presence of 0.8% starch (followed by hydrolysis of the starch with α-amylase), yielded CLEAs expressing high activity (immobilization yield around 100% and recovered activity around 80%), high effectiveness factor (approximately 65% of the equivalent free enzyme activity) and high stability at 40 °C and pH 8.0, i.e., PPL CLEAs co-aggregated with SMNPs/bovine serum albumin or SMNPs/soy protein retained 80% and 50% activity after 10 h incubation, respectively, while free PPL was fully inactivated after 2 h. Besides, highly porous magnetic CLEAs co-aggregated with soy protein and magnetic nanoparticles (pm-SP-CLEAs) showed good performance and reusability in the hydrolysis of tributyrin for five 4h-batches.